Damage in a large systemic lupus erythematosus cohort from the Spanish Society of Rheumatology Lupus Registry (RELESSER) with emphasis on the cardiovascular system: a longitudinal analysis - Altabás-González, Irene; Rua-Figueroa, Iñigo; Mouriño, Coral; Roberts, Karen; Jimenez, Norman; Martinez-Barrio, Julia; Galindo, María; Calvo Alén, Jaime; Pérez, Victor del Campo; Uriarte Itzazelaia, Esther; Tomero, Eva; Freire-González, Mercedes; et al. (Lupus science & medicine, 2024)
ObjectiveTo assess organ damage, with emphasis on the cardiovascular system, over the different stages of the disease in a large SLE cohort.MethodsMulticentre, longitudinal study of a cohort of 4219 patients with SLE enrolled in the Spanish Society of Rheumatology Lupus Registry. Organ damage was ascertained using the Systemic Lupus International Collaborating Clinics/American College of Rheumatology Damage Index (SDI). We longitudinally analysed SDI (globally and for each domain) over time only in the 1274 patients whose dates of damage events had been recorded.ResultsDuring the first year after diagnosis of SLE, 20% of the 1274 patients presented with new damage manifestations. At years 2 and 3, new damage was recorded in 11% and 9% of patients. The annual percentage of patients with new damage after year 5 decreased to 5%. In the first year with the disease, most damage was accumulated in the musculoskeletal, neuropsychiatric and renal systems; in later stages, most damage was in the musculoskeletal, ocular and cardiovascular systems. Considering ‘cerebrovascular accident’ and ‘claudication for 6 months’ as cardiovascular items, the cardiovascular system was the second most affected system during the early stages of SLE, with 19% of the patients who presented with damage affected at first year after diagnosis. During the late stages, 20–25% of the patients presenting with new damage did so in this modified cardiovascular domain of the SDI.ConclusionsNew damage occurs mainly during the first year following diagnosis of SLE. Cardiovascular damage is relevant in both the early and the late stages of the disease. Strategies to prevent cardiovascular damage should be implemented early after diagnosis of SLE.